PENGARUH STRUKTUR MODAL TERHADAP PAJAK PENGHASILAN BADAN TERUTANG PADA PERUSAHAAN SUB SEKTOR PERDAGANGAN ECERAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2020 - Silalahi, Evelin Roma Riauli; Sihotang, Helena; Nainggolan, Veronika (Jurnal Riset Akuntansi & Keuangan, 2023)
This study aims to determine the effect of capital structure (Longterm Debt to Asset Ratio and Debt to Equity Ratio) on corporate income tax payable in retail trading sub-sector companies listed on the Indonesian stock exchange in 2017-2020. The sample in this study was obtained by purposive sampling with a sample of 10 companies. The data collection technique used in this research is documentation. The analytical method used is multiple linear regression equation using SPSS 22. From the results of the SPSS test, it is known that the coefficient of determination (R square) is 0.421. This means that the capital structure (Longterm Debt to Asset Ratio and Debt to Equity Ratio) together affects the corporate income tax payable, which is 42.1%. Based on the results of multiple linear regression analysis, it can be concluded that the Longterm Debt to Asset Ratio has a significant negative effect on corporate income tax payable and the Debt to Equity Ratio has an insignificant positive effect on corporate income tax payable in retail trading sub-sector companies listed on the Indonesia Stock Exchange in 2017 -2020.